Correlation of maternal age with placenta previa - Anne Rose S, Arul; Gopalan, Ushadevi (International Journal of Medical Research and Review, 2015)
Objective: To study the effect of maternal age on incidence of placenta previa. Introduction: Placenta previa is a serious and life threatening obstetric complication where the placenta lies within the lower segment of the uterus, presenting an obstruction to the cervix and to delivery. A trend of increasing placenta previa incidence was observed in the past decade mainly because of an increasing caesarean section rate and advancing maternal age at the time of pregnancy. Methods: This study was a prospective study conducted in a teaching medical college and hospital over a period of two and a half years [2011- 2014]. A detailed history was taken according to our proforma for all pregnant women at or after 32 weeks who attended the hospital in the study period. As per inclusion and exclusion criteria of our study, the study population was selected. All other risk factors for placenta previa except maternal age were excluded. The association between maternal age and placenta previa was analysed. Placenta was located by Transabdominal ultrasound and patients with placenta previa were followed up regularly. Results: Our study showed that women aged ≥35 years or more had increased risk of placenta previa(3.6%) which was statistically significant (p<0.05) by Chi-square test. Conclusion- Advancing maternal age (≥ 35years) appears to increase the risk of placenta previa independent of other risk factors.